Natural Products as PI3K/ Akt Inhibitors: Implications in Preventing Hepatocellular Carcinoma - Narayanankutty, Arunaksharan (Current Molecular Pharmacology, 2021)
Hepatocellular carcinoma (HCC) is one of the prominent forms of cancer in developed countries. Globally, the incidence of HCC is well correlated with fatty liver disease and cirrhosis; the underlying chronic inflammation and lipotoxicity are thought to drive the process of HCC. Several biochemical cycles and molecular pathways are associated. The review aims to summarize the role of PI3K/Akt signaling and its downstream effectors in the development of HCC and its progression. Further, the emphasis has been given to the role of natural inhibitors of the PI3K/Akt pathway in HCC prevention, which are under various levels of drug discovery. The required literature were collected from PubMed/Medline databases, as well as Scopus or Web of science. It is evident that various signaling pathways activated by growth factors together with detoxification machinery and biochemical cycles converge to the PI3K/Akt signaling. The pathway plays a key role in the carcinogenesis, metastasis and drug resistance events of HCC cells and provides the growth and survival advantage. Natural products belonging to various classes such as terpenoids, flavonoids, saponins and stilbenoids are proven inhibitors of PI3K signaling and also found to inhibit HCC progression. PI3K/mTOR pathway inhibitors, especially the different phytochemicals, emerged as promising as anti-HCC agents. These molecules are shown to interfere with the PI3K signaling at various stages and therefore the PI3K targeted drugs may be a future for the chemotherapeutic arena.
Keywords: metastasis